Compartmental analysis of three-dimensional choroidal vascularity and thickness of myopic eyes in young adults using SS-OCTA - Luo, Huan; Sun, Jinfu; Chen, Lan; Ke, Dandan; Zhong, Zheng; Cheng, Xi; Yu, Huimin; Sun, Xufang (Frontiers in Physiology, 2022)
Purpose: To investigate the change of three-dimensional (3D) choroidal thickness (ChT), choroidal vessel volume (CVV), choroidal vessel index (CVI) in young myopic adults using swept-source optical coherence tomography angiography (SS-OCTA). To compare the difference of these indicators in different quadrants of macula and optic disc. Methods: A total of 248 eyes from 135 participants were enrolled in this cross-sectional study. Each participant underwent detailed history taking and ocular examinations. Based on axial length (AL), patients were divided into the emmetropia (EM) group, mild myopia (MIM) group, moderate myopia (MOM) group, and high myopia (HM) group. 6 mm×6 mm (1024×1024 B-scans) SS-OCTA scans were performed centered on the fovea and optic disc. 3D ChT, CVV and CVI were measured based on built-in deep learning algorithm. Differences of ChT, CVV and CVI were analyzed in different regions and different myopic groups. Results: Significant reduction in the global CVV were found in HM group (1.930 ± 0.865) in comparison with the EM (3.486 ± 0.992), MIM (3.238 ± 1.033) and MOM (2.589 ± 1.083) groups (P < 0.001). The global CVI was also lower in HM group (0.258 ± 0.061) compared to EM (0.320 ± 0.055), MIM (0.320 ± 0.051) and MOM (0.286 ± 0.066) groups (P < 0.001). The ChT was thinner in eyes with HM (242.753 ± 65.641) than in eyes with EM (377.532 ± 80.593), MIM (348.367 ± 78.191), or MOM (300.197 ± 87.175) (P < 0.001). Compartmental analysis revealed that ChT, CVV and CVI in nasal quadrant of the macula, temporal and inferior quadrants of the optic disc were much lower than other quadrants (P <0.05). Correlation analyses found that ChT, CVV and CVI were negatively correlated with AL and spherical equivalence. Conclusion: 3D ChT, CVV and CVI gradually decreased as the degree of myopia increased. The changes were more dramatical on the nasal side of the macula and on the temporal and inferior sides of the optic disc. These findings demonstrated the 3D choroidal change and highlighted papillo-macular bundle as a sensitive region in myopic development.